The Trajectory of Gender Based Violence (GBV) Impacts to Zimbabwean Children and Pathways for Child Safeguarding - Tatenda Nhapi; Takudzwa Mathende (Social Work & Society, 2018)
The inability of economic growth to meet the needs of a ballooning urban population which has 64% between the age of 18 and 35 and mostly unemployed has given rise to social pathology. This has been one Gender Based Violence (GBV) key driver. Consequently, GBV pervasiveness has been due to socio economic factors historically embedded in Zimbabwean way of life. The article relies on using the desk review research methodology targeting different commissioned reports, newspaper chapters and empirical research studies to explore the responses by various duty bearers, health and social welfare actors in this social pathological phenomena that has become embedded in most Zimbabwean urban and rural settings. Finally, pathways are offered on how best to robustly tackle SGBV whilst guaranteeing child welfare and safeguarding through tapping into the enabling legal and policy environment.